2015
DOI: 10.1002/cphc.201500477
|View full text |Cite
|
Sign up to set email alerts
|

Binding Selectivity of Macrocycle Ionophores in Ionic Liquids versus Aqueous Solution and Solvent‐free Conditions

Abstract: The understanding of supramolecular recognition in room-temperature ionic liquids (RTILs) is key to develop the full potential of these materials. In this work, we provide insights into the selectivity of the binding of alkali metal cations by standard cyclodextrin and calixarene macrocycles in RTILs. A direct laser desorption/ionization mass spectrometry approach is employed to determine the relative abundances of the inclusion complexes formed through competitive binding in RTIL solutions. The results are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It has been reported that metal cations can assist host/guest interactions and interact with CDs. , In a similar way, cationic bolaform heads are expected to interact with α-CD. The axle/CD complex should be considered as a transient along the reaction pathway for [2]­pseudorotaxane formation.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that metal cations can assist host/guest interactions and interact with CDs. , In a similar way, cationic bolaform heads are expected to interact with α-CD. The axle/CD complex should be considered as a transient along the reaction pathway for [2]­pseudorotaxane formation.…”
Section: Resultsmentioning
confidence: 92%